Determinants of individual relative deprivation amongst flight attendants - Mohd Ariffin, Siti Zubaidah; Ng, Siew Imm; Ho, Jo Ann; Murali, Sambasivan (Nilai Field Consultancy and Training, 2019)
This study examines the factors influencing Individual Relative Deprivation in the context of airline. Theory of Relative Deprivation was applied to explain the linkage between the Psychosocial Factors (Mental Health, Work-Family Conflict, Job Insecurity, Role Overload, and Pay Satisfaction) and Individual Relative Deprivation. The study followed quantitative research with cross sectional study design. Five hypotheses were formed suggesting mental health, work-family conflict, job insecurity, role overload, and pay satisfaction influence Individual Relative Deprivation. Based on purposive sampling, 410 usable samples were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM). All four proposed hypotheses were supported (mental health, work-family conflict, role overload, and pay satisfaction, while hypothesis suggesting job insecurity’s influence on Individual Relative Deprivation was not supported. Based on the findings, implications and future research directions were discussed.